Feasibility of awake endoscopic third ventriculostomy in selected patients of obstructive hydrocephalus. (2nd January 2023) - Sahoo, Sushant K.; Salunke, Pravin; Dhandapani, Sivashanmugam; Siroliya, Anshul; Jangra, Kiran
Abstract: Background: Endoscopic third ventriculostomy (ETV) is usually performed under general anesthesia (GA) with proper head immobilization. However a few patients with hydrocephalus (HCP) may not be suitable for GA. Once the surgeon is familiar with endoscopic ventricular anatomy and gains adequate surgical experience with the procedure, ETV can be attempted under local anesthesia (LA) in selected patients. Here we discuss our experience of treating 32 patients of HCP with ETV under LA. Methods: 32 symptomatic HCP patients with in the age range of 13 and 65 years, conscious, alert, cooperative and at high risk for GA owing to deranged liver or renal function, associated co-morbidities, pregnancy were considered for ETV under scalp block. All patients were evaluated for any discomfort during the surgical intervention. Result: All procedures were completed under LA. Four patients needed additional sedation prior to the scalp block to alleviate their apprehension. Four patients complained of bilateral orbital pain. In three it coincided with irrigation of fluid lower than body temperature. One patient had pain while touching the dorsum sella and needed analgesic supplement. All of them improved and none required additional CSF diversion within the average follow up of 9.5 months. Conclusion: ETV can be performed under local anesthesia in conscious, alert and cooperative patients in experienced hands. Unnecessary stimulation of the painful structures should be avoided and fluid for irrigation should be at body temperature. This ensures patient comfort and safety of the procedure.